Participatory Analysis and Evaluation of IPM Practices in Tomato (Indian Journal of Extension Education, 2010)
Farmers participatory trials were conducted for two years in four villages of two districts to identify the constraints in tomato cultivation and to introduce IPM technologies and evaluate their effectiveness through demonstration. Farmers identified nine constraints of which, increased severity of pests like fruit borer, leaf miner, cut worm and diseases like damping off, leaf curl and blight were the most important. Performance of eleven tomato varieties from various sources evaluated by farmers at their own field revealed that variety “Best of All” was best in preference, followed by “FI Hybrid 7610”. Implementation of IPM package involving Trichoderma, NPV, marigold, imidachlorpid, crop staking and poison bait led to nearly 50 per cent reduction in the usage of pesticides. In IPM plots, observation revealed reduction in severity of diseases like damping off (from 12.38 to 1.65 per cent), fusarium wilt (from 6.46 to 3.23 per cent) and blight (7.79 to 4.00 per cent) and incidence of insect pests like leaf miner (from 21.61 to 8.50), fruit borer ( from 12.88 to 5.75 per cent) and cutworm (10.36 to 3.84 per cent) when compared with non- IPM practices, four important component viz. Trichoderma applicant in nursery and main field, imidachlorpid (in nursery- root dip treatment and in main field), application of NPV and use of marigold (trap crop), staking of plants and use of poison bait were of significant importance since their impact was perceived to be maximum by farmers. Among the farmers perceived advantage of IPM , reduced incidence of insect pests and diseases was ranked the first followed by less plant mortality which resulted in optimum plant stand in field. Partial budget analysis revealed that the IPM practices increased the profit margin by Rs. 5498/ha in IPM plots when compared with the non- IPM plots.